“Raton” Edukasi Keragaman Budaya Indonesia Melalui Media Permainan Papan - Bimo Firstiawan Akbar; Samuel Gandang Gunanto; Arif Sulistiyono (Journal of Animation and Games Studies, 2019)
Lack of playground around the neighborhood and many of the children adolescent who play gadget more than playing an traditional games. “RATON” boardgame is a development of modified traditional games.There are processes that must be passed in the creation of boardgames such a concept, game rules, crafting, test play and packaging. The way to use it is almost the same as traditional Bentengan game, which is to seize the enemy fort by occupying it. It is complex in terms of regulations, but this games can be played by many people without leaving element made before this game exist.Keywords: boardgame, games, raton, traditional